Daschur, Ägypten - Alexanian, Nicole (e-Forschungsberichte des DAI, 2023)
The investigations of the valley temple, lower causeway and harbour of the Bent Pyramid (4th Dyn., 2.600 BC) at Dahshur were continued. In the upper part of the lower causeway a pedestrian underpass was discovered. An excavation and a magnetic survey showed that the brick building to the north of the valley temple of the Bent Pyramid predates the stone-temple and originally stood within an enclosure wall. Magnetic surveying further proved the existence of workmen‘s installations with planned ground layout in the wadi of the Bent Pyramid and south of the Red Pyramid.